Comparative analysis of PB2 residue 627E/K/V in H5 subtypes of avian influenza viruses isolated from birds and mammals - Briggs, Kelsey; Kapczynski, Darrell R. (Frontiers in Veterinary Science, 2023)
Avian influenza viruses (AIV) are naturally found in wild birds, primarily in migratory waterfowl. Although species barriers exist, many AIV have demonstrated the ability to jump from birds into mammalian species. A key contributor to this jump is the adaption of the viral RNA polymerase complex to a new host for efficient replication of its RNA genome. The AIV PB2 gene appears to be essential in this conversion as key residues have been discovered at amino acid position 627 that interact with the host cellular protein, acidic nuclear phosphoprotein 32 family member A (ANP32A). In particular, the conversion of glutamic acid (E) to a lysine (K) is frequently observed at this position following isolation in mammals. The focus of this report was to compare the distribution of PB2 627 residues from different lineages and origins of H5 AIV, determine the prevalence between historical and contemporary sequences, and investigate the ratio of amino acids in avian versus mammalian AIV sequences. Results demonstrate a low prevalence of E627K in H5 non-Goose/Guangdong/1996-lineage (Gs/GD) AIV samples, with a low number of mammalian sequences in general. In contrast, the H5-Gs/GD lineages sequences had an increased prevalence of the E627K mutation and contained more mammalian sequences. An approximate 40 percent conversion of E to K was observed in human sequences of H5 AIV, suggesting a non-exclusive requirement.Taken together, these results expand our understanding of the distribution of these residues within different subtypes of AIV and aid in our knowledge of PB2 mutations in different species.